Public Health Research Resulting from One of the World’s Largest Outbreaks Caused by Entero-Hemorrhagic Escherichia coli in Germany 2011: A Review - Köckerling, Elena; Karrasch, Laura; Schweitzer, Aparna; Razum, Oliver; Krause, Gérard (Frontiers in Public Health, 2017)
In 2011 Germany experienced one of the largest outbreaks of entero-haemorrhagic E. coli (EHEC) ever reported. Four years thereafter we systematically searched for scientific publications in PubMed and MEDPILOT relating to this outbreak in order to assess the pattern of respective research activities and to assess the main findings and recommendations in the field of Public Health. Following PRISMA guidelines we selected 133 publications, half of which were published within 17 months after outbreak onset. Clinical medicine was covered by 71, microbiology by 60, epidemiology by 46, outbreak reporting by 11 and food safety by 9 papers. Those on the last three topics drew conclusions on methods in surveillance, diagnosis, and outbreak investigation, on resources in public health, as well as on inter-agency collaboration, and public communication. Although the outbreak primarily affected Germany, most publications were conducted by multinational co-operations. Our findings document how soon and in which fields research was conducted with respect to this outbreak.